Dualistic Interpretation Toward Plague in Islam: Indonesian Muslim Responses and The Shifting of Worship Practices during Pandemic - Try Ramadhani, Moch. Rafly; Tsauro, M. Ahalla (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2023)
The Covid-19 pandemic that hit the world some time ago has affected a number of aspects in the life of mankind, including in the social interaction of the community. In Indonesia, Covid-19 has even led to policies on restrictions in worship practices. This article examines and critically evaluates the various interpretations and responses of religious organizations and Indonesian Muslims to the provisions of worship restrictions during the Covid-19 pandemic. Using a literature-based qualitative research method and a sociological approach, this article concludes that the different interpretations of Covid-19 among Muslim communities have played an important role in shaping responses and worship behavior during the pandemic. Some Muslims think rationally and interpret Covid-19 as a disaster and test of humanity. Based on this, they are more adaptive to government policies and regulations in carrying out worship. While some other Muslims who think fatalistically interpret Covid-19 as God’s punishment and destiny so they oppose health protocols. The different interpretations and responses of Muslims to the regulations on restrictions on worship during the Covid-19 pandemic are actually a continuation of the dualistic interpretation of the plague between rationalistic and fatalistic reasoning that has appeared in Islamic history. In today’s modern era, it is necessary to build a new paradigm that respects religious and scientific perspectives in a balanced manner so that it can transform from a dualistic approach to an integrative approach. Pandemi Covid-19 yang beberapa waktu lalu melanda dunia telah mempengaruhi sejumlah aspek dalam kehidupan umat manusia, termasuk dalam pergaulan sosial masyarakat. Di Indonesia, Covid-19 bahkan telah memunculkan kebijakan tentang pembatasan dalam praktik beribadah. Artikel ini mengkaji dan mengevaluasi secara kritis atas ragam interpretasi dan respons organisasi keagamaan serta umat Islam Indonesia terhadap ketentuan pembatasan ibadah selama pandemi Covid-19. Menggunakan metode penelitian kualitatif berbasis kepustakaan dan pendekatan sosiologis, artikel ini menyimpulkan bahwa perbedaan penafsiran terhadap Covid-19 di kalangan masyarakat muslim telah berperan penting dalam membentuk respons dan perilaku beribadah selama pandemi. Sebagian umat Islam berpikir rasional dan memaknai Covid-19 sebagai bencana dan ujian kemanusiaan. Atas dasar hal tersebut mereka bersikap lebih adaptif terhadap kebijakan dan aturan pemerintah dalam menjalankan ibadah. Sementara itu, sebagian umat Islam lainnya yang berpikir fatalistik dan menafsirkan Covid-19 sebagai hukuman dan takdir Tuhan sehingga mereka menentang protokol kesehatan. Perbedaan penafsiran dan respons umat Islam terhadap peraturan pembatasan beribadah selama pandemi Covid-19 tersebut sebenarnya merupakan kelanjutan dari penafsiran dualistik terhadap wabah antara penalaran rasionalistik dan fatalistik yang pernah muncul dalam sejarah Islam. Di era modern saat ini, perlu dibangun paradigma baru yang menghargai perspektif agama dan keilmuan secara berimbang sehingga mampu bertransformasi dari pendekatan dualistik menuju ke pendekatan integratif.